Coital frequency and condom use in age-disparate partnerships involving women aged 15 to 24: evidence from a cross-sectional study in KwaZulu-Natal, South Africa. Issue 3 (9th March 2019) - George, Gavin; Maughan-Brown, Brendan; Beckett, Sean; Evans, Meredith; Cawood, Cherie; Khanyile, David; Govender, Kaymarlin; Kharsany, Ayesha BM
Abstract : Objective: This study examines the role of age-disparate partnerships on young women's HIV risk by investigating coital frequency and condom use within age-disparate partnerships involving women aged 15 to 24. Design: A community-based, cross-sectional study was conducted. Setting: Participants were randomly selected using a two-stage random sampling method in uMgungundlovu district, KwaZulu-Natal, South Africa, between June 2014 and June 2015. Participants: A total of 1306 15–24-year-old women in an ongoing heterosexual partnership were included in the analysis. Participants had to be a resident in the area for 12 months, and able to provide informed consent and speak one of the local languages (Zulu or English). Primary and secondary outcome measures: Sexual frequency was assessed by asking participants how many times they had sex with each partner in the past 12 months. The degree of condomless sex within partnerships was assessed in the survey by asking participants how often they used a condom with their partners. Results: Age-disparate partnerships were associated with a higher order category (once, 2–5, 6–10, 11–20, >20) of coital frequency (adjusted OR (aOR) 1.32, p<0.05, 95% CI 1.02 to 1.71) and with sex on more than 10 occasions (aOR 1.48, p<0.01, 95% CI 1.12 to 1.96) compared with age-similar partnerships. Age-disparate partnerships were also more likely to involve sex on more than 10 occasions with inconsistent condom use (aOR 1.43, p<0.05, 95% CI 1.04 to 1.96) in the previous 12 months. Conclusion: The finding that increased sexual activity is positively associated with age-disparate partnerships adds to the evidence that age-disparate partnerships pose greater HIV risk for young women. Our study results indicate that interventions to reduce risky sexual behaviour within age-disparate partnerships remain relevant to reducing the high HIV incidence rates among adolescent girls and young women.